Diglosia poética: Vallejo / Verlaine - Ballón Aguirre, Enrique (2015)
Because the poetry of César Vallejo incorporates strategies poetic expression in which it moves away from the “ideal monolingual writing” and involves different levels of the Andean Castilian speech, it is a clear sign of a committed work with the multilingual character of the society in which it is inserted. Now, when Vallejo moved to Paris and changed its original Andean setting by French, only some of the early innovations were kept. In that sense, the purpose of this article is to show the ways in which it is evidence the change of Castilian-Quechua literary diglossia by the intervention of French in Vallejo’s poetry from the analysis of the poem untitled included in Poemas humanos.